Development of Website-Based Interactive Multimedia on the Topic of Glorifying Allah SWT by Obeying His Orders, PAI Subject Class VII SMP - Malik, muhammad Adam; Hendri, Nofri; Darmansyah, Darmansyah; Supendra, Dedi (Jurnal Ilmiah Mandala Education (JIME), 2024)
This research is a type of development research (Research and Development/R&D) carried out at SMP Muhammadiyah 6 Padang to overcome the problem of class VII Islamic Religious Education (PAI) learning which is still teacher-centered learning and does not involve students optimally. As a solution, website-based interactive multimedia was developed to increase student involvement. This research aims to develop and evaluate the validity and practicality of this multimedia. The ADDIE model, which consists of analysis, design, development, implementation and evaluation stages, is used in the development process. Validation by experts shows that this media is "very feasible" with a score of 4.88 for media and 4.68 for material. Implementation in class VII resulted in a practicality score of 4.20, which is also in the "very practical" category. The results show that this website-based interactive multimedia is suitable for implementation in PAI learning with the topic "Glorifying Allah SWT by Submitting to His Commands."